Thrombogenicity of Teflon versus copolymer-coated guidewires: evaluation with scanning electron microscopy. - Pinto, R S; Robbins, E; Seidenwurm, D (American Journal of Neuroradiology, 1989)
Utilizing the scanning electron microscope, we compared a new guidewire with copolymer coating with standard Teflon-coated, coiled-spring guidewires in both clinical and in vitro settings. Intense thrombogenicity was observed with the Teflon-coated guidewires with formed thrombi ranging in size from 50-100 microns. No formed thrombus was noted on any of the specimens of the copolymer guidewire, although isolated clumps of platelets and erythrocytes without fibrin strands were seen infrequently. We conclude that the copolymer guidewire is markedly less thrombogenic than Teflon-coated guidewires.